Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

Binomial combinatorics #1926

Merged
merged 18 commits into from
Apr 18, 2023
Merged
Show file tree
Hide file tree
Changes from all commits
Commits
File filter

Filter by extension

Filter by extension

Conversations
Failed to load comments.
Loading
Jump to
Jump to file
Failed to load files.
Loading
Diff view
Diff view
10 changes: 10 additions & 0 deletions CHANGELOG.md
Original file line number Diff line number Diff line change
Expand Up @@ -2020,6 +2020,16 @@ Other minor changes
allUpTo? : (P? : Decidable P) → ∀ v → Dec (∀ {n} → n < v → P n)
```

* Added new proofs in `Data.Nat.Combinatorics`:
```agda
[n-k]*[n-k-1]!≡[n-k]! : k < n → (n ∸ k) * (n ∸ suc k) ! ≡ (n ∸ k) !
[n-k]*d[k+1]≡[k+1]*d[k] : k < n → (n ∸ k) * ((suc k) ! * (n ∸ suc k) !) ≡ (suc k) * (k ! * (n ∸ k) !)
k![n∸k]!∣n! : k ≤ n → k ! * (n ∸ k) ! ∣ n !
nP1≡n : n P 1 ≡ n
nC1≡n : n C 1 ≡ n
nCk+nC[k+1]≡[n+1]C[k+1] : n C k + n C (suc k) ≡ suc n C suc k
```

* Added new proofs in `Data.Nat.DivMod`:
```agda
m%n≤n : .{{_ : NonZero n}} → m % n ≤ n
Expand Down
146 changes: 146 additions & 0 deletions src/Data/Nat/Combinatorics.agda
Original file line number Diff line number Diff line change
Expand Up @@ -12,11 +12,13 @@ open import Data.Nat.Base
open import Data.Nat.DivMod
open import Data.Nat.Divisibility
open import Data.Nat.Properties
open import Relation.Binary.Definitions
open import Relation.Binary.PropositionalEquality
using (_≡_; refl; sym; cong; subst)

import Data.Nat.Combinatorics.Base as Base
import Data.Nat.Combinatorics.Specification as Specification
import Algebra.Properties.CommutativeSemigroup as CommSemigroupProperties

open ≤-Reasoning

Expand Down Expand Up @@ -46,6 +48,15 @@ nPn≡n! n = begin-equality
where instance
_ = (n ∸ n) !≢0

nP1≡n : ∀ n → n P 1 ≡ n
nP1≡n zero = refl
nP1≡n n@(suc n-1) = begin-equality
n P 1 ≡⟨ nPk≡n!/[n∸k]! (s≤s (z≤n {n-1})) ⟩
n ! / n-1 ! ≡⟨ m*n/n≡m n (n-1 !) ⟩
n ∎
where instance
_ = n-1 !≢0

------------------------------------------------------------------------
-- Properties of _C_

Expand Down Expand Up @@ -85,3 +96,138 @@ nCn≡1 n = begin-equality
1 ∎
where instance
_ = n !≢0

nC1≡n : ∀ n → n C 1 ≡ n
nC1≡n zero = refl
nC1≡n n@(suc n-1) = begin-equality
n C 1 ≡⟨ nCk≡nPk/k! (s≤s (z≤n {n-1})) ⟩
(n P 1) / 1 ! ≡⟨ n/1≡n (n P 1) ⟩
n P 1 ≡⟨ nP1≡n n ⟩
n ∎


------------------------------------------------------------------------
-- Arithmetic of (n C k)

module _ {n k} (k<n : k < n) where

private

[n-k] = n ∸ k
[n-k-1] = n ∸ suc k

[n-k]! = [n-k] !
[n-k-1]! = [n-k-1] !

[n-k]≡1+[n-k-1] : [n-k] ≡ suc [n-k-1]
[n-k]≡1+[n-k-1] = +-∸-assoc 1 k<n


[n-k]*[n-k-1]!≡[n-k]! : [n-k] * [n-k-1]! ≡ [n-k]!
[n-k]*[n-k-1]!≡[n-k]! = begin-equality
[n-k] * [n-k-1]!
≡⟨ cong (_* [n-k-1]!) [n-k]≡1+[n-k-1] ⟩
(suc [n-k-1]) * [n-k-1]!
≡˘⟨ cong _! [n-k]≡1+[n-k-1] ⟩
[n-k]! ∎

private

n! = n !
k! = k !
[k+1]! = (suc k) !

d[k] = k! * [n-k]!
[k+1]*d[k] = (suc k) * d[k]
d[k+1] = [k+1]! * [n-k-1]!
[n-k]*d[k+1] = [n-k] * d[k+1]

[n-k]*d[k+1]≡[k+1]*d[k] : [n-k]*d[k+1] ≡ [k+1]*d[k]
[n-k]*d[k+1]≡[k+1]*d[k] = begin-equality
[n-k]*d[k+1]
≡⟨ x∙yz≈y∙xz [n-k] [k+1]! [n-k-1]! ⟩
[k+1]! * ([n-k] * [n-k-1]!)
≡⟨ *-assoc (suc k) k! ([n-k] * [n-k-1]!) ⟩
(suc k) * (k! * ([n-k] * [n-k-1]!))
≡⟨ cong ((suc k) *_) (cong (k! *_) [n-k]*[n-k-1]!≡[n-k]!) ⟩
[k+1]*d[k] ∎
where open CommSemigroupProperties *-commutativeSemigroup

k![n∸k]!∣n! : ∀ {n k} → k ≤ n → k ! * (n ∸ k) ! ∣ n !
k![n∸k]!∣n! {n} {k} k≤n = subst (_∣ n !) (*-comm ((n ∸ k) !) (k !)) ([n∸k]!k!∣n! k≤n)

nCk+nC[k+1]≡[n+1]C[k+1] : ∀ n k → n C k + n C (suc k) ≡ suc n C suc k
nCk+nC[k+1]≡[n+1]C[k+1] n k with <-cmp k n
{- case k>n, in which case 1+k>1+n>n -}
... | tri> _ _ k>n = begin-equality
n C k + n C (suc k) ≡⟨ cong (_+ (n C (suc k))) (k>n⇒nCk≡0 k>n) ⟩
0 + n C (suc k) ≡⟨⟩
n C (suc k) ≡⟨ k>n⇒nCk≡0 (m<n⇒m<1+n k>n) ⟩
0 ≡˘⟨ k>n⇒nCk≡0 (s<s k>n) ⟩
suc n C suc k ∎
{- case k≡n, in which case 1+k≡1+n>n -}
... | tri≈ _ k≡n _ rewrite k≡n = begin-equality
n C n + n C (suc n) ≡⟨ cong (n C n +_) (k>n⇒nCk≡0 (n<1+n n)) ⟩
n C n + 0 ≡⟨ +-identityʳ (n C n) ⟩
n C n ≡⟨ nCn≡1 n ⟩
1 ≡˘⟨ nCn≡1 (suc n) ⟩
suc n C suc n ∎
{- case k<n, in which case 1+k<1+n and there's arithmetic to perform -}
... | tri< k<n _ _ = begin-equality
n C k + n C (suc k)
≡⟨ cong (n C k +_) (nCk≡n!/k![n-k]! k<n) ⟩
n C k + (n! / d[k+1])
≡˘⟨ cong (n C k +_) (m*n/m*o≡n/o (n ∸ k) n! d[k+1]) ⟩
n C k + [n-k]*n!/[n-k]*d[k+1]
≡⟨ cong (_+ [n-k]*n!/[n-k]*d[k+1]) (nCk≡n!/k![n-k]! k≤n) ⟩
n! / d[k] + _
≡˘⟨ cong (_+ [n-k]*n!/[n-k]*d[k+1]) (m*n/m*o≡n/o (suc k) n! d[k]) ⟩
(suc k * n!) / [k+1]*d[k] + _
≡⟨ cong (((suc k * n!) / [k+1]*d[k]) +_) (/-congʳ ([n-k]*d[k+1]≡[k+1]*d[k] k<n)) ⟩
(suc k * n!) / [k+1]*d[k] + ((n ∸ k) * n! / [k+1]*d[k])
≡˘⟨ +-distrib-/-∣ˡ _ (*-monoʳ-∣ (suc k) (k![n∸k]!∣n! k≤n)) ⟩
((suc k) * n! + (n ∸ k) * n!) / [k+1]*d[k]
≡˘⟨ cong (_/ [k+1]*d[k]) (*-distribʳ-+ (n !) (suc k) (n ∸ k)) ⟩
((suc k + (n ∸ k)) * n !) / [k+1]*d[k]
≡⟨ cong (λ z → z * n ! / [k+1]*d[k]) [k+1]+[n-k]≡[n+1] ⟩
((suc n) * n !) / [k+1]*d[k]
≡˘⟨ /-congʳ (*-assoc (suc k) (k !) ((n ∸ k) !)) ⟩
((suc n) * n !) / (((suc k) * k !) * (n ∸ k) !)
≡⟨⟩
suc n ! / (suc k ! * (suc n ∸ suc k) !)
≡˘⟨ nCk≡n!/k![n-k]! [k+1]≤[n+1] ⟩
suc n C suc k ∎
where
k≤n : k ≤ n
k≤n = <⇒≤ k<n

[k+1]≤[n+1] : suc k ≤ suc n
[k+1]≤[n+1] = s≤s k≤n

[k+1]+[n-k]≡[n+1] : (suc k) + (n ∸ k) ≡ suc n
[k+1]+[n-k]≡[n+1] = m+[n∸m]≡n {suc k} [k+1]≤[n+1]

[n-k] = n ∸ k
[n-k-1] = n ∸ suc k

n! = n !
k! = k !
[k+1]! = (suc k) !
[n-k]! = [n-k] !
[n-k-1]! = [n-k-1] !

d[k] = k! * [n-k]!
[k+1]*d[k] = (suc k) * d[k]
d[k+1] = [k+1]! * [n-k-1]!
[n-k]*d[k+1] = [n-k] * d[k+1]
n!/[n-k]*d[k+1] = n ! / [n-k]*d[k+1]
[n-k]*n!/[n-k]*d[k+1] = [n-k] * n! / [n-k]*d[k+1]
[n-k]*n!/[k+1]*d[k] = [n-k] * n! / [k+1]*d[k]

instance
[k+1]!*[n-k]!≢0 = (suc k) !* [n-k] !≢0
d[k]≢0 = k !* [n-k] !≢0
d[k+1]≢0 = (suc k) !* (n ∸ suc k) !≢0
[k+1]*d[k]≢0 = m*n≢0 (suc k) d[k]
[n-k]≢0 = ≢-nonZero (m>n⇒m∸n≢0 k<n)
[n-k]*d[k+1]≢0 = m*n≢0 [n-k] d[k+1]